Phase II clinical trial testing the safety of a humanised monoclonal antibody anti-CD20 in patients with heart failure with reduced ejection fraction, ICFEr-RITU2: study protocol. Issue 3 (27th March 2019) - Sánchez-Trujillo, Luis; Jerjes-Sanchez, Carlos; Rodriguez, David; Panneflek, Jathniel; Ortiz-Ledesma, Claudia; Garcia-Rivas, Gerardo; Torre-Amione, Guillermo
Abstract : Introduction: Chronic heart failure with reduced ejection fraction (HFrEF) treatment targets neurohormonal inhibition; however, our experimental observations and the recent clinical evidence in myocardial infarction and heart transplant patients support the anti-inflammatory pathway as a potential novel therapeutic target. Therefore, we aimed to assess the safety of human monoclonal antibody-CD20 (rituximab) in patients with HFrEF. Methods and analysis: We designed this protocol according to the Standard Protocol Items: Recommendations for Interventional Trials guidelines as a phase II, single-centred, single group and prospective clinical trial. We hypothesise that the use of a monoclonal antibody, rituximab, could be a potentially safe new agent in HFrEF management. We will include patients with EF≤40%, New York Heart Association functional class III/IV and unresponsive to standard treatment. We will use a dosing regimen (1000 mg) previously applied to post-transplant patients and patients with rheumatoid arthritis with favourable results, aiming to provide supplementary evidence of safety in patients with HFrEF. We designed strategies tailored to preserving the integrity of patient safety. The date of study initiation will be 29th of May 2019. Ethics and dissemination: The following protocol was approved by IRB committees, and as a requirement, all patients need to sign an informed consent form before being subjected to any procedure prior to the initiation of the study. We are aware that the trial will be run in patients who due to their cardiovascular functional class, have reserved prognosis, with no known therapy that leads to improvement. Hence, this trial searches to establish the safety of an alternative strategy in ameliorating prognosis. Regardless of the study outcomes, whether favourable or not, they will be published. If a favourable outcome is evidenced, it will prompt performing a phase III, efficacy-based study. Trial registration number: The trial was approved by the IRB (CONBIOÉTICA-19-CEI-011–20161017 and COFEPRIS-17-CI-19-039-003), and registered at Clinicaltrials.gov (NCT03332888; Pre-Results ).